Left ventricular aneurysm: Twenty-year surgical experience with 1572 patients at the Texas Heart Institute - Reddy, Sitaram B. (1981)
From January 1958 through December 1979, 1572 patients underwent surgery for left ventricular aneurysm (LVA) in our institution. The series included 1365 men and 207 women, with a ratio of 6.5:1. Ages ranged from 25 to 79 years, with a mean of 54.7 years. Most patients were in NYHA functional Class III or IV, and all had sustained at least one documented myocardial infarction. During the first decade, LVA resection alone was performed, but after the advent of aortocoronary bypass (ACB) surgery, the majority of patients underwent ACB along with LVA resection. Some required additional septoplasty, mitral valve replacement, annuloplasty, or aortic valve replacement. In all groups, the mortality was higher for women than for men. Early deaths were due primarily to acute or progressive myocardial failure secondary to recurrent myocardial infarction. Follow-up information for 6 months to 8 years was obtained by means of questionnaires submitted to patients and referring physicians. Of 475 patients who underwent LVA resection and ACB and who responded, 92.2% were either improved or asymptomatic.